2022
DOI: 10.3390/microorganisms10040692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-Lethal Selection on Spontaneous Revertants of Frameshift Mutations: The Escherichia coli hisF Case

Abstract: Microorganisms possess the potential to adapt to fluctuations in environmental parameters, and their evolution is driven by the continuous generation of mutations. The reversion of auxotrophic mutations has been widely studied; however, little is known about the reversion of frameshift mutations resulting in amino acid auxotrophy and on the structure and functioning of the protein encoded by the revertant mutated gene. The aims of this work were to analyze the appearance of reverse mutations over time and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Each curve was performed in triplicate. The calculation of the areas under the growth curve (AUC) was obtained according to the chained trapezoidal rule [ 14 ]. Statistical significance of the differences between each condition was calculated through a non-parametric test and a post hoc analysis, Kruskal-Wallis and Dunn tests.…”
Section: Methodsmentioning
confidence: 99%
“…Each curve was performed in triplicate. The calculation of the areas under the growth curve (AUC) was obtained according to the chained trapezoidal rule [ 14 ]. Statistical significance of the differences between each condition was calculated through a non-parametric test and a post hoc analysis, Kruskal-Wallis and Dunn tests.…”
Section: Methodsmentioning
confidence: 99%
“…In order to check this hypothesis, the nucleotide sequence of each amplicon was Sanger sequenced, and the data obtained are summarized as follows: Seven revertants owned a wild-type hisF gene replacing the E. coli FB182 mutated one (group A). Based on the previous assumption (i.e., the very low probability, less than 4%, of spontaneous restoring of the correct sequence) [ 21 ], they should be the result of a recombination event involving a single copy of the wild-type hisF gene; Thirty-two revertants possessed two or more in tandem hisF copies (group B) and are the result of recombinational events involving one, two, or more copies of the donor DNA; Just one transformant was a chromosomal revertant owning a hisF gene with a restored frame but a different sequence from the wild-type one (group C), according to Del Duca et al [ 21 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Seven revertants owned a wild-type hisF gene replacing the E. coli FB182 mutated one (group A). Based on the previous assumption (i.e., the very low probability, less than 4%, of spontaneous restoring of the correct sequence) [ 21 ], they should be the result of a recombination event involving a single copy of the wild-type hisF gene;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that somatic assortment in P. tetraurelia occurs rather slowly, being prevented by the high ploidy of its macronucleus. In the second work, a histidine-auxotrophic mutant strain of E. coli , having a single-nucleotide deletion in its hisF gene, was used to study the effects of selective pressure on the reversion of frameshift mutations through a directed-evolution experiment [ 18 ]. The frequency of revertant mutants and the kind of mutation were finally correlated to the intensity of selective pressure, cultivation time, the tertiary structure of HisF, and ability to grow in the absence of His.…”
mentioning
confidence: 99%